Fulfillment of Nafkah For The Family Of The Tablighi Jamaat During Khuruj Fisabilillah (A Case Study of The Tablighi Jamaat In Medan) - Sukiati Sukiati; Pagar Pagar; Muhammad Edwan Roni; M. Fajri Syahroni Siregar (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2021)
This activity Tablighi Jamaat often raises people's questions about how to fulfill their family's nafkah during khuruj fisabilillah, especially those in the city of Medan, and how does it conform to the Positive Law and the Compilation of Islamic Law applicable in Indonesia. Through observation and interviews as primary data linked to the relevant literature, it was found that there were several cases whose livelihoods were not met. however a way of fulfilling a living has actually moved to the aspect of ukhuwah where members of the Tablighi Jamaat who are not khuruj actively provide material support to families who are left behind by khuruj fisabilillah, which is then called nusroh ahliyah so that in general efforts Fulfillment of family livelihoods when khuruj fisabilillah the ideal concept as it’s stated in Article 34 of Law no. 1 of 1974 concerning Marriage and Article 80 of the Compilation of Islamic Law, as well as the opinion of the scholars of the Shafi'i mazhab. However, it is suggested to the members of the Tablighi Jama'at that they should further improve their religious education for their family members so that they are mentally and spiritually living independently during the khuruj fisabilillah activities, and to the leaders of the Tablighi Jamaat to provide full and complete assistance at the stage before departure, so that there is no longer a family of Tablighi Jama'ah whose livelihood is neglected when they leave khuruj fisabilillah, so that they are able to give a very positive impression on the general public, especially the city of Medan